Towards a Suitable Micro-Takāful Plan in Malaysia: Benefits and Coverage Preferences of Low-Income B40 Groups - Nurul Aini Muhamed; Wahidah Shari; Asmadi Mohamed Naim; Mohamad Yazid Isa; Mohd Fikri Sofi; Selamah Maamor; Shahrul nizam Ahmad (International Centre for Education in Islamic Finance, 2026)
Indexed by Tier 2